Q. 7

# If 2y = 3 – 5x, find the value of y when x = –1.

We have,

2y = 3 – 5x

Now, by putting the value of x = - 1 in the given equation we get:

2y = 3 – 5 × (-1)

2y = 3 + 5

2y = 8

y = = 4

Hence, when x = - 1 then y = 4

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Quiz | Imp. Qs. on Coordinate Geometry39 mins
Coordinate Geometry45 mins
Coordinate Geometry37 mins
Basics of Coordinate Geometry43 mins
A Solid Grip on Basics of Coordinate Geometry49 mins
Quiz | Imp. Qs. of Coordinate Geometry46 mins
NCERT | Coordinate Geometry43 mins
A Solid Grip on Basics of Coordinate Geometry50 mins
Foundation I Solving Coordinate Geometry Questions50 mins
Marathon Quiz on Coordinate Geometry48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Draw the graph of the equation,

RS Aggarwal & V Aggarwal - Mathematics

Which point does not lie in any quadrant?

RS Aggarwal & V Aggarwal - Mathematics

Draw the graph of the equation,

RS Aggarwal & V Aggarwal - Mathematics

Draw the graph of the equation,

RS Aggarwal & V Aggarwal - Mathematics